Validation and Feasibility of Echocardiographic Assessment of Systemic Right Ventricular Function: Serial Correlation With MRI - Zandstra, Tjitske E.; Jongbloed, Monique R. M.; Widya, Ralph L.; ten Harkel, Arend D. J.; Holman, Eduard R.; Mertens, Bart J. A.; Vliegen, Hubert W.; Egorova, Anastasia D.; Schalij, Martin J.; Kiès, Philippine (Frontiers in Cardiovascular Medicine, 2021)
Background Inherent to its geometry, echocardiographic imaging of the systemic right ventricle (RV) is challenging. Therefore, echocardiographic assessment of systemic RV function may not always be feasible and/or reproducible in daily practice. Here, we aim to validate the usefulness of a comprehensive range of 32 echocardiographic measurements of systemic RV function in a longitudinal cohort by serial assessment of their correlations with cardiac magnetic resonance(CMR)-derived systemic RV ejection fraction (RVEF). Methods A single-center, retrospective cohort study was performed. Adult patients with a systemic RV who underwent a combination of CMR and echocardiography, both at two different points in time, were included. Offline analysis of echocardiographic images was blinded to offline CMR analysis and vice versa. In half of the echocardiograms, measurements were repeated by a second observer blinded to the results of the first. Correlations between echocardiographic and CMR measures were assessed with Pearson’s correlation coefficient and inter-observer agreement was quantified with intraclass-correlation coefficients (ICC). Results Fourteen patients were included, of which 4 with congenitally corrected transposition of the great arteries (ccTGA) and 10 patients with TGA late after atrial switch operation. Eight patients (57%) were female. There was a mean of 8 years between the first and second imaging assessment. Only global systemic RV function, fractional area change (FAC) and global longitudinal strain (GLS) were consistently, i.e. at both time points, correlated with CMR-RVEF (global RV function: r=-0.77/r=-0.63; FAC: r=0.79/r=0.67; GLS: r=-0.73/r=-0.70, all p<0.05). The ICC of GLS (0.82 at t=1, p=0.006, 0.77 at t=2, p=0.024) was higher than the ICC of FAC (0.35 at t=1, p=0.196, 0.70 at t=2, p=0.051) at both time points. Conclusion GLS appears to be the most robust echocardiographic measurement of systemic RV function with good correlation with CMR-RVEF and reproducibility.